Bildhafte Personenbezeichnungen: Desemantisierung und Resemantisierung deutscher Substantive im Spannungsfeld von Sexus und Genus - Di Meola, Claudio (Linguistik Online, 2024)
In German, there is a wide array of figurative designations for persons. They show various degrees of lexical complexity (simple nouns such as Sau, compounds such as Drecksau, collocations such as dreckige Sau) and different semantic domains of origin (mainly designation for animals – Sau – and inanimate objects – Flasche –, but also human beings – Strohmann –). They can refer specifically to females (Ziege, Besen), males (Windhund, Memme) or both (Kamel, Sau). Reference does not always coincide with grammatical gender. A complex interplay emerges between desemantization and resemantization processes: in the former, terms with a specific male or female reference develop unspecific reference for human beings including both sexes; in the latter, terms with originally unspecific reference come to refer to a single sex. In both processes a crucial role is played by lexical complexity, semantic (in)transparency and grammatical gender of the expression.